2013
DOI: 10.3109/02770903.2013.834931
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effects of domestic paints on asthma related symptoms in people with or without asthma

Abstract: The variable quality of the exposure assignment and heterogeneous study design makes it difficult to draw firm conclusions on whether domestic paint exposures cause or exacerbate asthma in children and/or adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, previous literature has suggested that indoor painting negatively affected allergic health in children (Canova et al, 2013;Mendell, 2007). However, previous literature has suggested that indoor painting negatively affected allergic health in children (Canova et al, 2013;Mendell, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, previous literature has suggested that indoor painting negatively affected allergic health in children (Canova et al, 2013;Mendell, 2007). However, previous literature has suggested that indoor painting negatively affected allergic health in children (Canova et al, 2013;Mendell, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The study was intended to show the effect of new painting in old school classrooms on allergic health in real-life school environment. However, previous literature has suggested that indoor painting negatively affected allergic health in children (Canova et al, 2013;Mendell, 2007). Among indoor chemicals emitted from indoor painting and drying, various VOCs could enhance allergic diseases in children (Chin et al, 2014;Rumchev et al, 2004;Tagiyeva and Sheikh, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the European Community Respiratory Health Survey, asthma in children was positively associated with the presence of higher indoor concentration of the VOCs acetaldehyde and toluene (Hulin, Caillaud, & Annesi-Maesano, 2010). Several reviews have concluded there is insufficient research to evaluate the impact of VOCs on asthma control (Canova, Jarvis, Walker, & Cullinan, 2013;Institute of Medicine, 2000;Nurmatov, Tagieva, Semple, Devereux, & Sheikh, 2013;Tagiyeva & Sheikh, 2014). The impact of VOCs on asthma control and quality of life in older adults has not been explored.…”
Section: Chemical Emissions From Common Indoor Materials Are Associmentioning
confidence: 99%
“…Respiratory health effects of (indoor) VOCs have been the subject of research scrutiny. Several review articles and meta-analyses have already been published [14][15][16]. However, there remains limitations to these studies.…”
Section: Introductionmentioning
confidence: 99%